Excitation-contraction coupling in mammalian skeletal muscle: Blending old and last-decade research - Bolaños, Pura; Calderón, Juan C. (Frontiers in Physiology, 2022)
The excitation–contraction coupling (ECC) in skeletal muscle refers to the Ca2+-mediated link between the membrane excitation and the mechanical contraction. The initiation and propagation of an action potential through the membranous system of the sarcolemma and the tubular network lead to the activation of the Ca2+-release units (CRU): tightly coupled dihydropyridine and ryanodine (RyR) receptors. The RyR gating allows a rapid, massive, and highly regulated release of Ca2+ from the sarcoplasmic reticulum (SR). The release from triadic places generates a sarcomeric gradient of Ca2+ concentrations ([Ca2+]) depending on the distance of a subcellular region from the CRU. Upon release, the diffusing Ca2+ has multiple fates: binds to troponin C thus activating the contractile machinery, binds to classical sarcoplasmic Ca2+ buffers such as parvalbumin, adenosine triphosphate and, experimentally, fluorescent dyes, enters the mitochondria and the SR, or is recycled through the Na+/Ca2+ exchanger and store-operated Ca2+ entry (SOCE) mechanisms. To commemorate the 7th decade after being coined, we comprehensively and critically reviewed “old”, historical landmarks and well-established concepts, and blended them with recent advances to have a complete, quantitative-focused landscape of the ECC. We discuss the: i) elucidation of the CRU structures at near-atomic resolution and its implications for functional coupling; ii) reliable quantification of peak sarcoplasmic [Ca2+] using fast, low affinity Ca2+ dyes and the relative contributions of the Ca2+-binding mechanisms to the whole concert of Ca2+ fluxes inside the fibre; iii) articulation of this novel quantitative information with the unveiled structural details of the molecular machinery involved in mitochondrial Ca2+ handing to understand how and how much Ca2+ enters the mitochondria; iv) presence of the SOCE machinery and its different modes of activation, which awaits understanding of its magnitude and relevance in situ; v) pharmacology of the ECC, and vi) emerging topics such as the use and potential applications of super-resolution and induced pluripotent stem cells (iPSC) in ECC. Blending the old with the new works better!